Javna občila na narodnostno mešanem območju v Lendavi - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1993)
The authoress analyses the data on the frequency of mass media usage and the satisfying of needs for information, education and entertainment by means of mass media in the ethnically mixed region of Lendava. Comprised in the article are the majority nation media, the Hungarian minority media and the parent state media. The data are processed by means of statistical procedures,the result of which are determined values of factors and testing of statistical hypotheses.
Keywords: javno obveščanje; Madžari; mediji; množični mediji; narodne manjšine; Prekmurje; Slovenija